Urban road traffic deaths: data linkage and identification of high-risk population sub-groups - Lúcia Maria Miana Mattos Paixão; Eliana Dias Gontijo; Sueli Aparecida Mingoti; Dário Alves da Silva Costa; Amélia Augusta de Lima Friche; Waleska Teixeira Caiaffa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Abstract This study analyzes the profile of deaths from road traffic accidents in Belo Horizonte, Minas Gerais State, Brazil, by linking two public databases, the Information System of the Urban Transportation and Transit Company (BH10) and the Mortality Information System (SIM). The linked database (n = 306) identified a 24% under-recording rate for deaths and differed in the age distribution from the BH10 database and in roadway user category when compared to the mortality database. The mortality rate for road traffic accidents within the city limits was 10.2 per 100,000 thousand, and was higher among men, young adults, and the elderly. Poisson multivariate regression showed a higher mean death rate for motorcycle occupants (rate ratio - RR: 1.81); pedestrians (RR: 1.32); males (RR: 1.24); single/divorced (RR: 1.27); young adults 18-29 years of age (RR: 1.75); elderly (RR: 1.59); and deaths at the crash site (RR: 1.39) when compared to the reference categories. The study unveils the city's traffic violence, expressed by the large proportion of deaths at the crash site and within the first 24 hours, and confirms the relevance of database linkage for characterizing vulnerable groups and traffic accident mortality in the urban setting.